2021
DOI: 10.2147/nss.s278088
|View full text |Cite
|
Sign up to set email alerts
|

Current Understanding of the Chronobiology of Cluster Headache and the Role of Sleep in Its Management

Abstract: Cluster headache is uniquely rhythmic in its occurrence both diurnally and annually. This has implications for the clinical approach to the patient but also for our understanding of the role of central structures in its pathological basis. Many intrinsic and extrinsic factors seem to influence CH rhythmicity, including genetics. The proclivity for attacks to occur at night and the possible association with particular sleep phenomena, including sleep apnea, have motivated a number of studies which has improved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 107 publications
0
20
0
Order By: Relevance
“…Overall, studies exploring the sleep phases in CH patients showed: (1) irregular sleep–wake patterns; (2) a decreased total amount of sleep; (3) a decreased proportion of REM sleep; (4) a prolongation of REM latency; and (5) a condition of hypoarousability during REM sleep in bouts [ 6 , 37 ]. Nevertheless, further studies failed to prove an association between CH attacks and REM sleep [ 38 , 39 , 40 ]. The evidence about the association between REM sleep and CH attacks is conflicting even if REM sleep may not represent a prerequisite for CH attacks, since they have been observed during other sleep phases, too [ 40 ].…”
Section: Sleep Disorders and Chmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, studies exploring the sleep phases in CH patients showed: (1) irregular sleep–wake patterns; (2) a decreased total amount of sleep; (3) a decreased proportion of REM sleep; (4) a prolongation of REM latency; and (5) a condition of hypoarousability during REM sleep in bouts [ 6 , 37 ]. Nevertheless, further studies failed to prove an association between CH attacks and REM sleep [ 38 , 39 , 40 ]. The evidence about the association between REM sleep and CH attacks is conflicting even if REM sleep may not represent a prerequisite for CH attacks, since they have been observed during other sleep phases, too [ 40 ].…”
Section: Sleep Disorders and Chmentioning
confidence: 99%
“…Nevertheless, further studies failed to prove an association between CH attacks and REM sleep [ 38 , 39 , 40 ]. The evidence about the association between REM sleep and CH attacks is conflicting even if REM sleep may not represent a prerequisite for CH attacks, since they have been observed during other sleep phases, too [ 40 ]. Such evidence could support previous hypotheses that the beginning and the end stages of sleep may represent the more vulnerable phases [ 6 , 41 ].…”
Section: Sleep Disorders and Chmentioning
confidence: 99%
“…Despite the negative findings, the orexin system remains a potential target in migraine prevention as well as narcolepsy, and future trials will likely focus on medications with more selective activity on specific orexin receptors. Cluster and hypnic headache also seem to involve pathophysiology related to hypothalamic control over circadian rhythm as evidenced by attack risk often predictably varying based on time of day, neuroimaging abnormalities in the hypothalamus, the therapeutic role of melatonin and lithium, and secretory laboratory abnormalities 48 . The comorbidity of these primary headache disorders and sleep disorders including narcolepsy, insomnia, and sleep apnea have been explored in some limited samples, but this connection merits further study.…”
Section: Sleep Disordersmentioning
confidence: 99%
“…The pathogenesis of this disease is, at the current state of knowledge, based on the derangement of the complex interactions existing between the trigeminovascular system activating the trigeminal-autonomic reflex, leading to the release of specific neuropeptides like calcitonin gene-related peptides (CGRP) and pituitary adenylate cyclase-activating polypeptide 38 (PACAP-38), and its interactions with a deranged (putative) hypothalamic control center [5,6]. Further multiple basic and clinical research approaches have added important information on the role of neurosteroids, neuroimaging and neurophysiology data, sleep disorders, and psychiatric comorbidities in this still not completely clear pathophysiological picture of CH [7][8][9][10].…”
Section: Cluster Headache the Cinderella Among The Primary Headachesmentioning
confidence: 99%